On the Accuracy of Ray‐Theory Methods to Determine the Altitudes of Intracloud Electric Discharges and Ionospheric Reflections: Application to Narrow Bipolar Events. Issue 9 (4th May 2020) - Li, Dongshuai; Liu, Feifan; Pérez‐Invernón, F. J.; Lu, Gaopeng; Qin, Zilong; Zhu, Baoyou; Luque, Alejandro
Abstract: Narrow bipolar events (NBEs) (also called narrow bipolar pulses [NBPs] or compact intracloud discharges [CIDs]) are energetic intracloud discharges characterized by narrow bipolar electromagnetic waveforms identified from ground‐based very low frequency (VLF)/low‐frequency (LF) observations. The simplified ray‐theory method proposed by Smith et al. (1999, https://doi.org/10.1029/1998JD200045 ; 2004, https://doi.org/10.1029/2002RS002790 ) is widely used to infer the altitude of intracloud lightning and the effective (or virtual) reflection height of the ionosphere from VLF/LF signals. However, due to the large amount of high‐frequency components in NBEs, the propagation effect of the electromagnetic fields for NBEs at large distance depends nontrivially on the geometry and the effective conductivity of the Earth‐ionosphere waveguide (EIWG). In this study, we investigate the propagation of NBEs by using a full‐wave Finite‐Difference Time‐Domain (FDTD) approach. The simulated results are compared with ground‐based measurements at different distances in Southern China, and we assess the accuracy of the simplified ray‐theory method in estimating the altitude of the NBE source and the effective reflection height of the ionosphere. It is noted that the evaluated NBE altitudes have a slight difference of about ±1 km when compared with the full‐wave FDTD results, while the evaluated ionospheric reflection heights are found to be bigger than those obtained from FDTD model by about 5 km. Key Points: The propagation effect of NBEs is analyzed using full‐wave model and compared with measurement The simplified ray‐theory method might require correction comparing to the full‐wave model We quantify errors in the ionospheric height evaluated from the Smith method